Financing the Infrastructure of Municipal Corporation on Sustainable Basis: A Case Study of Vasai Virar Municipal Corporation - Sanjay RODE (Management and Economics Review, 2023)
Every Municipal Corporation must provide administrative services and develop infrastructure for people. The Vasai Virar Municipal Corporation is the fastest growing Municipal Corporation in the Mumbai Metropolitan Region. Urbanization is increasing rapidly in corporations, but infrastructure services are lagging behind. There is a mismatch between the revenue and expenditure of the corporation. The revenue receipts are significantly low due to lower property taxes and road construction. The revenue expenditure is increasing due to administration, architecture section, accounts, hospitals management, and construction sector. The capital receipts are significantly lower because of integrated health and family welfare receipts. The capital expenditure of the corporation has increased due to road repairing and construction, development work, and electricity expenditure. The municipal corporation must invest in civic infrastructure such as water supply, sanitation, solid waste and sewerage management, roads, public transportation, public gardens, street lights, and markets. Municipal Corporations must manage capital expenditure on a sustainable basis for civic infrastructure. It will improve the standard of living of the people.